Relationship between lead in the blood and performance in the abilities from hearing process - de Moraes, Tamyne Ferreira Duarte; Gonçalves, Thaís dos Santos; Salvador, Karina Krähembühl; Lopes, Andréa Cintra; Alvarenga, Kátia de Freitas; Feniman, Mariza Ribeiro (Arquivos Internacionais de Otorrinolaringologia, 2012)
Introduction: The contamination by lead affects all the nervous systems from the human body, mostly the nervous system.Objective: Investigate if there is correlation between the blood lead levels and the performance in tests of hearing process.Method: Retrospective study. 73 children, with ages between 7 to 15 years, residents in a area where happened emission of lead above the permitted, with level of blood lead level bigger or equal to 10 micrograms/dL, audiological exams (audiometry and tympanometry) inside the normality patterns. To evaluate the hearing process were used the Auditory Fusion Test-Revised (AFT-R), subtest 1, and the dichotic test of digits (binaural integration stage). Was used the Spearman test to verify the correlation between the data.Results: The blood lead level varieties from 10 to 30,2 micrograms/dL, being the average corresponding to 15,8 micrograms/dL (standard deviation of 4,8). From those children, 60,3% presented a bad performance for the right ear and 67,3% presented a bad performance of the left ear. According to the results of the tests of correlation of Spearman, there were no significant statistical between the level of lead and the results of hearing processing tests.Conclusion: There were no correlation between the blood lead level and the performance in the abilities of the hearing process; however the contaminated children by the lead presented a lower performance in the abilities of the hearing processing.
Keywords: lead; hearing; children; phonoaudiology; comprehension